Synthesis and crystal structure of-(3S,10S,13S,17S)-N-(2-methoxyphenyl)-10,13-dimethyl-17-((R)-1-(p-tolylamino)ethyl)hexadecahydro-1H-cyclopenta[α]phenanthren-3-amine, C35H50N2O - Yang Mei; Wei Peng; Sun Yi-Chun; Ye Jiang-Hai; Zou Juan; He Kang (Zeitschrift für Kristallographie - New Crystal Structures)
C35H50N2O, orthorhombic, P212121 (no. 19), a = 6.7114 Å, b = 19.6699(9) Å, c = 22.7057(10) Å, V = 2,997.4(2) Å3, Z = 4, Rgt(F) = 0.0401, wRref(F2) = 0.0995, T = 297(2) K.